They Stole Him Out of Jail : Willie Earle, South Carolina's Last Lynching Victim - Gravely, William, 1939- (Book collections on Project MUSE., 2019)
"Over the last quarter century, a surge in scholarship about lynching in the United States coincided with a discussion by professional historians about why the topic had long suffered from neglect. New research has made possible a more complete picture of South Carolina's lynching history. The first major study, Terence Finnegan's 1993 dissertation, compared lynching in South Carolina and Mississippi. In 2006 John Hammond Moore set lynching in the state alongside murder and dueling over four decades after 1880. Two years later a Pickens County native and professor in an English university, Bruce Baker, used a case-study approach to compare seven lynchings in the two Carolinas from Reconstruction to 1930. All have drawn upon the earlier research of two master's students who surveyed twentieth-century in-state lynchings"--